Perception of local health functionaries regarding the impact of COVID-19 on health-seeking behaviour of presumptive tuberculosis patients in tricity - Dhiman, Shivani; Goel, Naveen Krishan; Prashar, Savita; Rana, Kirtan (International Journal Of Community Medicine And Public Health, 2023)
Background: The COVID-19 pandemic has affected every domain of human life globally and has presented an unprecedented challenge to public health, work, education, and social life. The healthcare services were prioritized and indirectly affected by that. The current study assumed the perception of healthcare functionaries regarding the impact of COVID-19 on the health-seeking behavior of presumptive TB patients in tricity (Chandigarh, Panchkula, and Mohali). Methods: A concurrent mixed method study design was conducted among 100 randomly selected healthcare functionaries from public health facilities in tricity. A self-structured and validated questionnaire was used and analyzed using SPSS v24 by both qualitative (frequencies, Chi-square, odd ratio) and quantitative (themes) approach. Results: Among 100 respondents 62% participants responded that there was a disruption of the normal functioning of testing and treatment under the National Tuberculosis Elimination Program (NTEP). The logistics and manpower were shifted to COVID-19 management and testing of PTB patients was mostly affected. The in-depth interview found that factors like social stigma, downplaying of TB disease, and less knowledge about TB were the reasons behind the disruption of PTB services. The health functionaries also gave suggestions for the betterment of PTB services if these kinds of pandemics arise in the future. Conclusions: Having national programs such as NTEP should be not kept on back foot while dealing with the pandemic, as TB is considered to be the greatest challenge for Health System and human beings as well.